Metabolic engineering of E. coli for pyocyanin production - Silva, Adilson Jose da; Cunha, Josivan de Souza; Hreha, Teri; Micocci, Kelli Cristina [UNESP]; Selistre-de-Araujo, Heloisa Sobreiro; Barquera, Blanca; Koffas, Mattheos A. G. (Elsevier B.V., 2021)
Pyocyanin is a secondary metabolite from Pseudomonas aeruginosa that belongs to the class of phenazines, which are aromatic nitrogenous compounds with numerous biological functions. Besides its antifungal and antimicrobial activities, pyocyanin is a remarkable redox-active molecule with potential applications ranging from the pharma industry to the development of microbial fuel cells. Nevertheless, pyocyanin production has been restricted to P. aeruginosa strains, limiting its practical applicability. In this study, the pyocyanin biosynthetic pathway was engineered for the first time for high level production of this compound in a heterologous host. Escherichia coli cells harboring the nine-gene pathway divided into two plasmids were able to produce and secrete pyocyanin at higher levels than some Pseudomonas aeruginosa strains. The influence of culture and induction parameters were evaluated, and the optimized conditions led to an increase of 3.5-fold on pyocyanin accumulation. Pathway balancing was achieved by testing a set of plasmids with different copy numbers to optimize the expression levels of pyocyanin biosynthetic genes, resulting in a fourfold difference in product titer among the engineered strains. Further improvements were achieved by co-expression of Vitreoscilla hemoglobin Vhb, which relieved oxygen limitations and led to a final titer of 18.8 mg/L pyocyanin. These results show promise to use E. coli for phenazines production, and the engineered strain developed here has the potential to be used in electro-fermentation systems where pyocyanin plays a role as electron-shuttle.
Keywords: Pyocyanin; Phenazines; Pseudomonas aeruginosa; Pathway balance; Vitreoscilla hemoglobin